Adolescents' Perceptions About Dating and Sexual Permissiveness in Ebonyi State, Nigeria: What Can Be Done to Enhance Adolescents' Sexual Health and Well-Being - Ezumah, Nkoli; Agu, Ifunanya Clara; Okeke, Chinyere; Agu, Chibuike; Mbachu, Chinyere Ojiugo; Onwujekwe, Obinna (Frontiers in Reproductive Health, 2021)
Introduction: Adolescent sexual and reproductive health (SRH) issues constitute key health concerns as some adolescents are directly or indirectly involved in sexual engagements, with increased risks and health consequences. The study aims to explore adolescents' perceptions about dating and permissive sexual behaviors which will contribute to designing sexual and reproductive health interventions. This paper adds to knowledge on adolescents' perceptions about dating, pre-marital, casual, transactional and age-disparate sex in southeastern, Nigeria. Methods: A qualitative study was undertaken in the three senatorial zones of Ebonyi state, south eastern Nigeria. The study population comprised unmarried in- and out-of-school adolescents aged 13–18 years. Data were collected using a pre-tested focus group discussion (FGD) guide. There were six FGDs for boys and six FGDs for girls. A thematic framework approach was used for data analysis. Results: Adolescents' views about dating and other sexual behaviors were varied. The dominant view is that hugging, touching and kissing are inappropriate for unmarried adolescents. Similarly, pre-marital, casual, transactional, and age-disparate sex were viewed as unacceptable. However, some adolescents perceived pre-marital abstinence as a hindrance to the attainment of sexual satisfaction and reproductive capacity in marriage. Some boys and girls indicated that casual sex is good, because it enables girls from poor homes to socialize with more privileged boys/men, and that such relationships could lead to marriage. Some considered transactional and age-disparate sex as a means of survival from poverty and unemployment. Boys were more permissive in their views about sexual behaviors compared to the girls. Conclusion: Adolescents' perceptions of sexual behaviors as acceptable/unacceptable vary and are gendered. This should be considered in designing innovative strategies to improve adolescents' sexual health and well-being.